PENGARUH KESEIMBANGAN KEHIDUPAN-KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA PADA DOSEN MILENIAL FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Noerin Fajar Yusvia (2021)
This study is a quantitative study that aims to determine the effect of work-life balance and work stress on job satisfaction for millennial lecturers. The sample used in this research is 39 millennial lecturers at the Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta. Data collection is carried out through the distribution of google forms which are distributed through online platforms. The analysis technique used is the inferential analysis method and processing data through SmartPLS with a significant level of 5% or 0.05. The results of the tests carried out showed that the work-life balance variable had a significant effect on the job satisfaction variable because it had a t-count value greater than the t-table value (2.255 > 1.688) and a significance value of 0.025 > 0.05. Then the work stress variable has a significant and significant effect on job satisfaction because it has a t-count value greater than the t-table value (2.247 > 1.688) and a significance value of 0.035 <0.05. Meanwhile, simultaneously, the work-life balance variable and work stress have a significant and significant effect on the job satisfaction variable because the calculated f value is greater than f table (54 > 3.26) and the significant value is 0.000 < 0.05.